EPISODE PERJUANGAN BANGSA DALAM JURNALISME KORAN JAWA POS DALAM RUBIK “HOAX ATAU BUKAN” - Aditya, Krisna (JURNAL KEBANGSAAN RI, 2024)
In an era when information does not only come from journalists, but also from various media platforms and even from ordinary people, there is a lot that we consider as "information". Sometimes there is so much, we ignore and get lost in the truth of the information. Now there is the internet and social media, now printed newspapers are not the main source for citizens to obtain information. However, there is a principle that the Jawa Pos newspaper carries out, namely the educational function carried out by the Jawa Pos newspaper to prevent the spread of hoaxes with the rubric "Hoax or Not". This research uses a qualitative method with a case study approach to the "Hoax or Not" column of the Jawa Pos newspaper. Mass media can play a role in educating the public about the importance of media literacy and how to recognize false information. This includes providing guidance on how to check sources, recognize bias, and evaluate the credibility of news stories. This research concludes that the “Hoax or Not” column can maintain high standards of ethical journalism, such as not publishing unverified information or refraining from sensationalism, building trust with their audience and positioning themselves as a reliable source of information. In the current context, it helps reduce the spread of false information and increases public literacy awareness about the importance of fact verification.